Evaluation of Phytochemical and Pharmacological Activity of Carissa carandas L. Fruits at Three Different Stages of Maturation - Saher, Shabnam; Narnawre, Smita; Patil, Jayshree (Drug Research, 2020)
Inflammation plays an important role in various diseases with high prevalence within populations such as rheumatoid arthritis, ulcer, atherosclerosis and asthma. Many drugs are available in the market for inflammatory diseases but they exhibit several unwanted side effects. Therefore, alternative treatments with safer compounds are needed. The plant Carissa carandas L. plant is used traditionally for the treatment of various diseases. Hence to validate its traditional use, the present study has envisaged screening different solvents extract of Carissa carandas fruit for their phytochemical and pharmacological activity especially the anti-inflammatory activity of the fruits at 3 different stages of maturation. The n-hexane and chloroform extracts of immature, mature and ripe fruits showed positive tests for steroids and triterpenoids, whereas acetone extract showed positive tests for steroids, triterpenoids, alkaloids, tannins, sugar, saponins except for triterpenoids in immature fruits. The hydroalcoholic extract showed presence of alkaloids, tannins, sugars, saponin and flavonoids. The highest concentration of phenol, flavonoids and ascorbic acid were found to be more in acetone extract of mature fruits and of carbohydrates in ripe fruits. The hydroalcoholic extract also exhibited similar pattern. The anti-inflammatory property was evaluated by using different models like carrageenan induced paw edema in Wistar rats and cotton pellets induced granuloma. There was a consistent increase in % inhibition of inflammation at concentrations of 100 and 200 mg/kg up to 3 h. The highest activity was at 3 h with 200 mg/kg dose. Thus the present work has clearly proved that the acetone extract of mature fruits have considerable anti-inflammatory activity.
Keywords: inflammation; carissa carandas; anti-inflammatory; phytochemical; carrageenan